2013
DOI: 10.1264/jsme2.me13034
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for Complex Microbial Ecosystems: Combination of Experimental Approaches with Mathematical Modeling

Abstract: In the past couple of decades, molecular ecological techniques have been developed to elucidate microbial diversity and distribution in microbial ecosystems. Currently, modern techniques, represented by meta-omics and single cell observations, are revealing the incredible complexity of microbial ecosystems and the large degree of phenotypic variation. These studies propound that microbiological techniques are insufficient to untangle the complex microbial network. This minireview introduces the application of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 69 publications
1
14
0
Order By: Relevance
“… Kato et al (2005 , 2008 ) constructed model microbial consortia composed of 4–5 bacterial strains, in which all members stably coexisted for long period of time, and demonstrated that existence of both positive and negative interspecies interactions among the members make these consortia stable. The construction of model consortia is a specific and beneficial feature of microbiological research fields, which will also be effective for proof-of-concept studies for theories in the field of macro-ecology ( Haruta et al, 2009 , 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“… Kato et al (2005 , 2008 ) constructed model microbial consortia composed of 4–5 bacterial strains, in which all members stably coexisted for long period of time, and demonstrated that existence of both positive and negative interspecies interactions among the members make these consortia stable. The construction of model consortia is a specific and beneficial feature of microbiological research fields, which will also be effective for proof-of-concept studies for theories in the field of macro-ecology ( Haruta et al, 2009 , 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…strains YN07 and chemo52. Almost all of the kinetic parameters for phenol of the individual strains were similar to those from the soil bioreactor as described previously (Haruta et al, 2013 ). The K S -values varied within one order of magnitude (from 1 to 10 μM), whereas the K I -values varied within two orders of magnitude (from 100 to 1000 μM).…”
Section: Resultsmentioning
confidence: 93%
“…In a soil bioreactor fed with phenol we previously observed a unique phenomenon where the kinetic parameters shifted toward higher K S and lower K I -values (Futamata et al, 2005 ; Haruta et al, 2013 ). In the present study, to understand this unique phenomenon, SMEs were constructed using isolated strains exhibiting different phenotypic features.…”
Section: Discussionmentioning
confidence: 98%
“…In this article, we review various mathematical approaches developed for simulating microbial community dynamics. While a number of published studies have offered insightful perspectives on this subject (e.g., [12][13][14][15][16][17][18]), the present review is unique in the following aspects. First, instead of being confined to specific applications, we cover a wide range of frameworks developed for modeling diverse systems such as biofilms, biogeochemical cycling (in soil or ocean), human microbiota, biotechnology processes, etc.…”
Section: Introductionmentioning
confidence: 99%